Utilization of eucalyptus bark powder as low-cost adsorbent for the removal of methylene blue dyes from wastewater and comparison with activated charcoal - Verma, Kiran; Khare, Amit (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Dyes and pigments have been used in many industries for coloration purposes. There is a considerable need for the removal of colour from wastewater or effluents from dye industries. The use of low-cost and eco-friendly adsorbents had been investigated as an ideal alternative to the current expensive methods of removing dyes from wastewater. The aim of this study is to investigate the adsorption potential of Eucalyptus Bark Powder as a low cost adsorbent for Methylene Blue (MB) dye, and compare the result with Charcoal Powder (standard adsorbent).The adsorption was studied of different Methylene Blue (MB) dye concentration using batch technique. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->